2013
DOI: 10.1007/s13577-012-0057-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Hand-Foot Syndrome induced by PEG-modified liposomal Doxorubicin

Abstract: PEGL-DOX is an excellent treatment for recurrent ovarian cancer that rarely causes side-effects like cardiotoxicity or hair loss, but frequently results in Hand-Foot Syndrome (HFS). In severe cases, it can become necessary to reduce the PEGL-DOX concentration or the duration of the drug therapy, sometimes making it difficult to continue treatment. In this study, we prepared an animal model to compare the effects of DOX versus PEGL-DOX, and we noticed that only treatment with PEGL-DOX resulted in HFS, which led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 14 publications
1
56
0
1
Order By: Relevance
“…Jacobi et al (14) reported the appearance of PPE only in patients with hyperhidrosis of these regions. Another hypothesis is that PPE develops due to an excessive concentration of toxic doxorubicin within the skin and its reaction with metal ions (particularly copper ions) (15). An underlying mechanism for the development of other skin disorders is poorly known.…”
Section: Discussionmentioning
confidence: 99%
“…Jacobi et al (14) reported the appearance of PPE only in patients with hyperhidrosis of these regions. Another hypothesis is that PPE develops due to an excessive concentration of toxic doxorubicin within the skin and its reaction with metal ions (particularly copper ions) (15). An underlying mechanism for the development of other skin disorders is poorly known.…”
Section: Discussionmentioning
confidence: 99%
“…The pegylated liposome-encapsulated DOX form has low cardiotoxicity, but high skin and oral toxicity (hand-foot syndrome [HFS]) are induced partly because of extravasation of the liposomes due to long circulation time. 4,5 Therefore, in addition to pegylated liposome-encapsulated form of DOX, the use of non-pegylated liposomal (NPL)-DOX is also predominant in chemotherapy. 6 NPL-DOX as a component of the R-CHOP regimen is a highly effective treatment in patients with diffuse large B cell lymphoma and pre-existing cardiac diseases.…”
Section: Introductionmentioning
confidence: 99%
“…25 The HFS is partly caused by extravasation of the liposomes due to long circulation time. 5 The presence of targeting aptamer in our ApDC system could probably reduce the nonspecific circulatory time and enhance the tumor distribution and permeation, making it possible to reduce HFS symptoms compared to pegylated liposome-encapsulated DOX.…”
mentioning
confidence: 99%
“…For example, the reduced nephrotoxicity of liposomal amphotericin B 30 and the reduced cardiotoxicity of pegylated liposomal doxorubicin 37 are reflected in the reported side effects, as is the occurrence of hand-foot syndrome because of the pegylation of doxorubicin. 35 The reduced cardiotoxicity of liposomal daunorubicin has not been confirmed in comparative clinical trials but is supposed to be present based on other liposomal studies for anthracyclines. 15 The lower toxicological profile of liposomal cytarabine compared to conventional cytarabine could not be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in reporting between pegylated liposomal and conventional doxorubicin is mainly caused by the hand-foot syndrome (palmar-plantar erythrodysesthesia) including neuropathy, which is a side effect of multiple chemotherapeutic agents, but more so for PEG-modified liposomal chemotherapeutic preparations. 35 Overall, there are certain specific side effects associated with pegylated doxorubicin compared to regular doxorubicin, of which some can be related to the properties of the nanoformulation. In addition to the hand-foot syndrome for PEG-modified chemotherapeutics mentioned earlier, pegylated therapeutics can also cause unexpected immunemediated side effects.…”
mentioning
confidence: 99%